Cloning DPB3, the gene encoding the third subunit of DNA polymerase II of Saccharomyces cerevisiae. - Araki, H (1991)
DNA polymerase II purified from Saccharomyces cerevisiae contains polypeptides with apparent molecular masses of greater than 200, 80, 34, 30 and 29 kDa, the two largest of which (subunits A and B) are encoded by the essential genes POL2 and DPB2. By probing a lambda gt11 expression library of yeast DNA with antiserum against DNA polymerase II, we isolated a single gene, DPB3, that encodes both the 34- and 30-kDa polypeptides (subunit C and C'). The nucleotide sequence of DPB3 contained an open reading frame encoding a 23-kDa protein, significantly smaller than the observed molecular masses, 34- or 30-kDa, which might represent post-translationally modified forms of the DPB3 product. The predicted amino acid sequence contained a possible NTP-binding motif and a glutamate-rich region. NTP-binding motif and a glutamate-rich region. A dpb3 deletion mutant (dpb3 delta) was viable and yielded a DNA polymerase II lacking the 34- and 30-kDa polypeptides. dpb3 delta strains exhibited an increased spontaneous mutation rate, suggesting that the DPB3 product is required to maintain fidelity of chromosomal replication. Since a fifth, 29-kDa polypeptide was present in DNA polymerase II preparations from wild-type cell extracts throughout purification, the subunit composition appears to be A, B, C (or C and C') and D. The 5' nontranscribed region of DPB3 contained the MulI-related sequence ACGCGA, while the 0.9-kb DPB3 transcript accumulated periodically during the cell cycle and peaked at the G1/S boundary. The level of DPB3 transcript thus appears to be under the same cell cycle control as those of POL2, DPB2 and other DNA replication genes. DPB3 was mapped to chromosome II, 30 cM distal to his7.